Assessment of Growth Monitoring Activities under Integrated Child Development Programme (ICDS) in Vadodara District of Gujarat State - Suraj I. Kuriya; Dhara I Zalavadiya; Jivraj Damor; Vihang S. Mazumdar (Indian Association of Preventive and Social Medicine, 2020)
Introduction: The Integrated Child Development Services (ICDS) programme is implemented through a network of community-level Anganwadi centers (AWCs). The range of services includes growth monitoring, immunization, health check-ups, and supplementary feeding, nutrition and health education. The study was done with the objective to assess the knowledge and skill of Anganwadi workers (AWWs) regarding growth monitoring at AWCs under ICDS. Method: It was a cross-sectional study conducted in 63 AWCs under field practice area of Rural Health Training Centre (RHTC) of the medical college. Knowledge and skill about growth monitoring were assessed by Knowledge Assessment Score (KAS) and Skill Assessment Score (SAS) respectively. Results: Mean KAS was 10.4 out of 15 whereas Mean SAS found to be 8.32 out of 10. Knowledge of AWWs regarding various topics like sources for getting birth date of child, procedure for weighing child, malnutrition grade by growth chart plotting and interpretation of various malnutrition grades was poor. Whereas understanding of various aspect of growth monitoring like when to start growth monitoring, how to weigh a child, interpretation of growth curve was good. Conclusion: Knowledge and skill regarding growth monitoring was lacking among AWWs. Training should be organized with continuous supportive supervision so that knowledge can be converted into skilful practices.